Financial risk attitudes, demographic profiles, and behavioural traits: Do they interrelate? - Abd Sukor, Mohd Edil; Nasehi, Payam; Koh, Eric H.Y (Asian Journal of Accounting Perspectives, 2021)
Research aim: The paper addressed two objectives: examining the differences in behavioural traits with regard to risk attitudes, and explore the differences in financial risk attitudes with regard to demographic profiles of Malaysian investors. Design/ Methodology/ Approach: Using the t-test and one-way analysis of variance (ANOVA), this paper investigates how differences in behavioural trait bias among 241 master of business administration students in Malaysia affect their financial risk attitudes. Research finding: First, we find that the financial risk takers have higher levels of overconfidence, maximization, happiness, and trust than the risk-averse respondents. Second, in terms of demographics, we find that the following take significantly higher risks: men versus women, singles versus those who are married, and, those with lower income and less work experience. Besides, in terms of race, the Chinese are the greatest financial risk takers. Theoretical contribution/ Originality: Both the behavioural traits and financial risk attitudes are new for a multicultural background market like Malaysia. Reflections on the findings suggest that the financial planners need to take cognisance of such relationships, tendencies and risk preferences so as to understand their client inclination and provide appropriate advice to their investor clients. Research limitation/ Implication: Categories under the research design and sample selection can be further extended by considering more advanced research approach and a bigger size of sample respondents. Keywords: Behavioural Finance, Behavioural Traits, Risk Attitudes, Financial Risk, Demographic Profiles Type of article: Research paper JEL Classifications: D14, D91, G41 Received: 31 January 2020 Revised: 15 April 2020, 24 April 2020 Accepted: 6 May 2020 Published online: 29 January 2021